On complete accumulation points of discrete subsets - Ofelia T. Alas; Richard G. Wilson (Applied General Topology, 2007)
We introduce a class of spaces in which every discrete subset has a complete accumulation point. Properties of this class are obtained and consistent examples are given to show that this clas sdiffers from the class of countably compact and the class of compact spaces. A number of questions are posed.